Association between oxidative balance score and metabolic syndrome and its components in US adults: a cross-sectional study from NHANES 2011–2018 - Lu, Yi; Wang, Meixiang; Bao, Jiaxin; Chen, Dashuang; Jiang, Hao (Frontiers in Nutrition, 2024)
Background Metabolic syndrome (MetS) is a global health concern that threatens human well-being. The oxidative balance score (OBS) is a tool to identify the level of oxidative stress that is correlated with MetS risk. However, association between OBS and MetS and its components has not been reported. Methods This cross-sectional study included adult individuals with complete OBS and MetS data from National Health and Nutrition Examination Survey (NHANES) 2011–2018. A weighted logistic regression analysis was conducted to identify the association of the total, dietary, and lifestyle OBS scores with MetS. Subgroup analyses and restricted cubic splines were used to further explore associations. Results In total, 10,025 eligible adult individuals (51.48% were males at a median age of 46 years) were included, with a MetS prevalence of 29.98%. In fully adjusted model, higher total OBS was associated with reduced risk of MetS (Q3 vs. Q1: odds ratio [OR] = 0.57, 95% confidence interval [CI], 0.46–0.71, p < 0.001; Q4 vs. Q1: OR = 0.42, 95% CI, 0.33–0.53, p < 0.001; P for trend <0.001). Significant differences were observed in the relationship between dietary OBS and lifestyle OBS and MetS risk (continuous dietary OBS: OR = 0.97, 95% CI, 0.96–0.98, p < 0.001; continuous lifestyle OBS: OR = 0.61, 95% CI, 0.58–0.64, p < 0.001), as well as negative relationship between total OBS and risk of five MetS components (all p < 0.05). Subgroup analysis showed marital status modified the negative association between OBS and MetS in subgroup analysis (P for interaction = 0.014). Moreover, a nonlinear correlation between OBS and MetS (including its components) was found, further elucidating associations (all p < 0.05). Restricted cubic splines demonstrated not obviously U-shape correlation between OBS and MetS components (elevated triglyceride and blood pressure). Conclusion This study suggests a strong association between the OBS and MetS and its components. Our data indicated that a higher OBS score was correlated with a decreased risk of MetS and its components in a nonlinear manner. Hence, the OBS may serve as an effective marker for identifying individuals with MetS, with a higher score indicating a predominance of more antioxidants.